1968
DOI: 10.1002/1097-0142(196809)22:3<525::aid-cncr2820220306>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Medroxyprogesterone acetate in the treatment of renal cell carcinoma (hypernephroma)

Abstract: Medroxyprogesterone acetate, a potent synthetic progestational steroid, was administered to 23 patients with metastatic renal cell carcinoma. Seven patients received 300 mg/d orally. Six patients received 100 mg/d intramuscularly of the commercial preparation Provera. Ten patients were given 400 mg/w intramuscularly of an investigational preparation. Twenty‐one patients completed a minimum treatment period of 6 weeks and were considered evaluable. There were one complete and two partial objective remissions to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1971
1971
1985
1985

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In this situation Between 70 and 80 per cent of all malignant kidney Bloom (4), Samuels (5), Paine (6) and Brühl(l) have tumours are renal cell carcinomas (1). Even if at the time drawn attention to the possibility of achieving significant of nephrectomy no distant metastases can be detected, tumour regression in a limited number of patients with about 50 per cent of the patients die within 5 years after renal carcinoma by administering steroid hormones.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation Between 70 and 80 per cent of all malignant kidney Bloom (4), Samuels (5), Paine (6) and Brühl(l) have tumours are renal cell carcinomas (1). Even if at the time drawn attention to the possibility of achieving significant of nephrectomy no distant metastases can be detected, tumour regression in a limited number of patients with about 50 per cent of the patients die within 5 years after renal carcinoma by administering steroid hormones.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with advanced cases not treated with hormones this is a conservative figure, since the duration of life in the present series had been measured from the onset of hormone therapy which in many patients was introduced some time after the appearance of recurrent tumour. It appears that an objective response of renal carcinoma to hormone therapy is accompanied by prolongation of life, a conclusion also reached by Samuels et al (1968).…”
Section: Dijration Of Life In Hormone-treated Casesmentioning
confidence: 83%
“…It is interesting to note that progestin-induced histological changes in cases of endometrial cancer were observed within only 4 weeks in 75% of responding cases: in the remaining 25% such changes were delayed for 8-12 weeks (Sherman, 1966). On the other hand, experience elsewhere with renal cancer has indicated that signs of improvement may not appear until 2 months after starting hormone therapy (Samuels et al, 1968;Paine et al, 1970). Talley and his colleagues (1969) had to wait as long as 5 and 8 months before observing regression in their two cases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations